2011
DOI: 10.1143/apex.4.083101
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Spot Detection Model in Superconducting Nano-Stripline Detector for keV Ions

Abstract: Superconducting nano-stripline detectors (SSLDs) are promising for realizing ideal ion detection in mass spectrometry. We have investigated the ion detection efficiency of a niobium nitride (NbN) SSLD, measuring the bias current dependence of the detection efficiency for Ar þ , Ar 2þ , and Ar 3þ ions accelerated by static voltages between 0.5 and 3 kV. The bias current dependence exhibited a distinct plateau in a high bias region and an abrupt reduction at a certain bias current (threshold bias current) that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…The experiment by Suzuki et al [14] on ion detection in 800 nm wide, 10 nm thick, detectors has clearly demonstrated that the normal-core hot spot model is correct in the keV range. This is understandable, as a single injection of a large amount of energy will be enough to break all the Cooper pairs at a single position along the wire, leading to a normal-core scenario.…”
Section: Fig 4 (Color Online)mentioning
confidence: 97%
See 2 more Smart Citations
“…The experiment by Suzuki et al [14] on ion detection in 800 nm wide, 10 nm thick, detectors has clearly demonstrated that the normal-core hot spot model is correct in the keV range. This is understandable, as a single injection of a large amount of energy will be enough to break all the Cooper pairs at a single position along the wire, leading to a normal-core scenario.…”
Section: Fig 4 (Color Online)mentioning
confidence: 97%
“…DOI: 10.1103/PhysRevLett.112.117604 PACS numbers: 79.20.Ws, 03.65.Wj, 85.25.Oj Nanowire superconducting single photon detectors (SSPDs or SNSPDs) [1,2] are currently the most promising detection systems in the infrared, achieving detection efficiencies of up to 93% at 1550 nm [3]. Despite these technological advances, the fundamentals of the working principle of these detectors are poorly understood and under active investigation, both theoretically [4][5][6][7][8][9][10][11] and experimentally [12][13][14][15][16][17][18][19][20][21][22].A typical SSPD consists of a few nm thin film of a superconducting material such as NbN or WSi, nanofabricated into a meandering wire geometry. When biased sufficiently close to the critical current of the superconductor, the energy of one or several photons can be enough to trigger a local transition to the resistive state, resulting in a detection event.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For very high photon 5 or particle energies, 42 the contribution of excess QPs outside the normal conducting volume is probably negligible, but they may become significant or even dominating for smaller excitation energies. This was first realized in the QP-model 12 which does not require a normal conducting volume.…”
Section: B Detection Criteriamentioning
confidence: 99%
“…As briefly mentioned in section 2.3, the charge state derivation by SSPDs can be understood by the hotspot model, in which the diameter of hotspots are proportional to the square root of the kinetic energies of ions. [17] The curves of the detection efficiency as a function of bias current show abrupt reductions at certain bias currents that depend on the ionic charge states and are defined as threshold bias currents (I th ) for detecting ions. The experimental I th was found to follow I th /I c = 1 -(zeV) 1/2 C/w, where C is the factor determined by the density of states at the Fermi level in principle.…”
Section: Charge Discrimination and True Mass Spectrometrymentioning
confidence: 99%